The unconsciousness of the female discipline ideology – analysis of the symptoms of the three poems of Qingping Tune from the perspective of feminism - Ziliang Huo (Trans/Form/Ação)
In this paper, from the perspectives of feminism, through the analysis of Li Bai’s inheritance and innovation of palace-style poetry in his creation, the author puts forward two techniques and their symptom in the three poems of Qingping Tune: inheriting the sensationalization of palace-style poetry and innovating in the mythological and legendary techniques of palace-style poetry. Based on these two techniques, the unconsciousness of the fetish and goddess mythological fantasy is revealed from the “blankness” of the image itself, so as to achieve the research effect of a comprehensive analysis of the female discipline ideology in the aristrocrats’ patriarchal courtly literature.